2018
DOI: 10.1016/j.jhydrol.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The onshore influence of offshore fresh groundwater

Abstract: Thus, offshore freshwater should be assessed in coastal water balances presuming that it serves as an existing freshwater input, rather than as a new potential freshwater resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Preferential flow paths can enhance connectivity relative to homogeneous aquifers in systems with karst conduits (Evans & Lizarralde, ; Xu et al, ), palaeochannels (Mulligan et al, ), natural faults (Varma & Michael, ), and a range of other heterogeneous geologic settings (Houben et al, ; X. Li et al, ; Michael et al, ). Knight et al () analyzed 27 coastal sites globally and found that widespread losses of offshore freshwater are associated with onshore pumping due to connections between offshore and onshore fresh groundwater reserves. One example is Gippsland Australia, where offshore pumping has caused onshore resource conflicts (Figure b) and drawdowns have reached up to 50 m in 40 years (Varma & Michael, ).…”
Section: Introductionmentioning
confidence: 99%
“…Preferential flow paths can enhance connectivity relative to homogeneous aquifers in systems with karst conduits (Evans & Lizarralde, ; Xu et al, ), palaeochannels (Mulligan et al, ), natural faults (Varma & Michael, ), and a range of other heterogeneous geologic settings (Houben et al, ; X. Li et al, ; Michael et al, ). Knight et al () analyzed 27 coastal sites globally and found that widespread losses of offshore freshwater are associated with onshore pumping due to connections between offshore and onshore fresh groundwater reserves. One example is Gippsland Australia, where offshore pumping has caused onshore resource conflicts (Figure b) and drawdowns have reached up to 50 m in 40 years (Varma & Michael, ).…”
Section: Introductionmentioning
confidence: 99%
“…ast offshore bodies of fresh and moderately brackish groundwater (concentration of total dissolved solids of <10 g l −1 ) have been documented up to 100 km from modern shorelines and down to 4.5 km below the seafloor (bsf) 1 . The majority of offshore freshened groundwater (OFG) is hosted in shallow (<300 m), poorly consolidated, clastic sediments in seawater depths less than 50 m [1][2][3] . Nearly all discoveries of OFG have been made along passive continental margins, mostly in the Atlantic US and European margins 4,5 .…”
mentioning
confidence: 99%
“…These include active groundwater migration across topographic gradients via present day, permeable connections between offshore and onshore aquifers 6 , recharge during Pleistocene sealevel lowstands 7,8 , sub-glacial and pro-glacial injection 9 , entrapment of connate water in subsiding basins 10 , and gas hydrate dissociation 11 . Global volumetric estimates of OFG were derived in passive margins and are on the order of 10 5 km 3 . This is two orders of magnitude greater than the volume of groundwater that has been extracted globally from continental aquifers since 1900 (refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent analytical and SEAWAT (Langevin et al, 2008) modeling studies underline the importance of heterogenic geological conditions (mainly presence and extension of aquitards) on potential OFGV occurrence (Van Engelen et al, 2018;Knight et al, 2018;Morgan et al, 2018;Solórzano-Rivas and Werner, 2018), turning away from earlier simulations embedding homogeneous geological conditions (Ranjan et al, 2009;Michael et al, 2013;Werner et al, 2013;Ketabchi et al, 2016) and moving toward more complex heterogeneous subsurface representation (e.g., Michael et al, 2016;Zamrsky et al, 2018;Thomas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%